Yacon (Smallanthus sonchifolius): Effect on Integrity of Intestinal Barrier, Inflammatory Response and Oxidative Stress in Animal Model of Colon Cancer (P06-052-19) - Costa, Neuza (Curr Dev Nutr, 2019)
OBJECTIVES: To investigate the prebiotic effect of yacon, source of fructooligosaccharides (FOS), on the integrity of the intestinal barrier, inflammatory response and oxidative stress in rats with induced colon cancer. METHODS: 44 adult Wistar rats were distributed into 4 groups: S (without colon cancer and yacon; n = 10); C (with colon cancer without yacon; n = 12); Y (without colon cancer with yacon; n = 10); and CY (with colon cancer and yacon; n = 12). Animals of groups S and C received AIN-93 M diet and animals of groups Y and CY received the same diet but added with yacon flour containing 28.95% FOS, to provide 5% FOS in the diet, for 16 weeks. From week 4 to 8, the animals of C and CY groups received an intraperitoneal dose of 25 mg/kg body weight of 1.2-dimethylhydrazine (DMH-Sigma®) once a week. In the last week, 24h-urine collection was performed for intestinal permeability analysis using lactulose and mannitol. Blood sample was collected for the analysis of IL-10 and IL-12 cytokines (Milliplex® Map, Luminex®) and total antioxidant capacity - TAC (Elabscience®). Large intestine was collected for intraluminal pH, short chain fatty acids - SCFA (HPLC) and immunoglobulin A – sIgA (Cloud-Clone®) analysis. Normal distributed data were analyzed by Two-way ANOVA, followed by Newman-Keuls (p < 0.05), using GraphPad Prism®, version 7. RESULTS: Cancer-induced animals showed higher TNF-α, SCFA (acetate, propionate and butirate), and lower TAC. Yacon reduced intraluminal pH and lactulose/mannitol ratio, increased propionic acid in the feces, but showed no effect on IL-10, IL-12, TNF-α, and IL-10/IL-12 ratio. The levels of sIgA were increased only in the group fed yacon without cancer (group Y). Mannitol and TAC were higher in CY group, showing a significant interaction of yacon and colon cancer. CONCLUSIONS: Yacon reduced pH, intestinal permeability and the oxidative stress associated with colon cancer. The local immunity (sIgA) was raised, although no effect was observed on cytokines with yacon consumption. Yacon is a rich source of FOS wich improves the intestinal barrier and mucosal immunity, particularly in healthy animals. FUNDING SOURCES: CNPq, FAPES.